Comparative study of microdebrider-assisted turbinoplasty and partial turbinectomy in hypertrophic rhinitis: Cohort data from Vietnamese patients - Chau, Hoa Chieu; Pham, Cong Thanh; Nguyen, Chan Quoc Dang; Duong, Nghi Huu; Ngo, Gia Hoang (Acta Biomedica Atenei Parmensis, 2025)
Background and Aim: Hypertrophic rhinitis of the inferior turbinate is characterized by persistent enlargement of the mucosal, submucosal, and bony components of the inferior turbinate, severely affecting the patient’s quality of life. This study examines the clinical and subclinical features of patients with inferior turbinate hypertrophy requiring surgery and compares microdebrider-assisted turbinoplasty with partial turbinotomy. Methods: We conducted a prospective comparative cohort study with a historical control of 155 patients from April 2016 to June 2024. Patients were assigned to undergo either microdebrider-assisted turbinoplasty (MAIT group, n = 68) or partial inferior turbinotomy (PIT group, n = 87). Evaluations were conducted one week, one month, and three months after surgery. Results: The study included 155 patients with an average age of 34.9 ± 11.4 years and a male-to-female ratio of 2:1. At the one-week follow-up, the MAIT group showed a significantly greater reduction in Nasal Obstruction Symptom Evaluation (NOSE) scores (45.7 ± 19.2 vs. 37.1 ± 15.7, P = 0.003), with notable differences in nasal crusting and inferior edema. Endoscopic evaluation showed better wound healing in the MAIT group (92.6%) than in the PIT group (74.7%, P = 0.005). However, at the three-month follow-up, there were no significant differences in NOSE score reduction or endoscopic findings (all P-values > 0.05) between the two groups. Conclusions: Microdebrider-assisted inferior turbinoplasty and partial inferior turbinotomy are very effective surgical techniques for treating hypertrophy of the inferior turbinate and related problems of nasal obstruction. Microdebrider-assisted inferior turbinoplasty ensures both size reduction and maximum preservation of the inferior turbinate mucosa.